Light-shading high-barrier-property composite film capable of replacing aluminizing and preparation method of light-shading high-barrier-property composite film
By using a composite film composed of a base layer, a light-shielding layer, an ultraviolet-proof layer and a protective layer in the packaging material, the problems existing in the production, use and recycling of traditional aluminum-coated films are solved, and packaging materials with high light-shielding, strong ultraviolet-proof and environmentally friendly properties are achieved.
Patent Information
- Application Number
- CN202411741514.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
Traditional aluminum-coated films have high energy consumption, high environmental pollution during production, insufficient adhesion, easy to fall off during use, and difficult to recycle and handle, which cannot meet the demands of high-end packaging market for light shading, UV protection and environmental protection performance.
A composite film consisting of a base layer, a light-shielding layer, an ultraviolet-proof layer and a protective layer is used. The light-shielding layer is made of montmorillonite nanoclay, polymer and nanoscale titanium dioxide dispersion. The ultraviolet-proof layer is prepared by extrusion casting process, coating and spraying process using bio-based materials and benzene compounds or triazole compounds as ultraviolet absorbers.
It achieves high light-shading and strong UV protection performance, reduces production costs, reduces environmental pollution, improves the durability and aesthetics of packaging, and is suitable for the high-end packaging market.
Smart Images

Figure BDA0005162698840000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of composite film preparation, and in particular to a composite film with high light-shielding barrier properties and capable of replacing aluminum plating, and a preparation method thereof. Background Art
[0002] With the rapid development of the packaging industry, the requirements for packaging materials are also increasing. Traditional aluminized film is widely used due to its good light-shielding and UV-proof properties, but it has some shortcomings. In the packaging industry, aluminized film is widely used due to its good light-shielding and UV-proof properties. However, with the advancement of technology and the enhancement of environmental awareness, the production and use of aluminized film has gradually exposed a series of problems.
[0003] First of all, the production process of aluminum film has high energy consumption and great environmental pollution. The aluminum plating process consumes a lot of electricity and heat energy, and also produces a lot of wastewater, waste gas and solid waste, causing serious pollution to the environment. This not only increases production costs, but also violates the principle of sustainable development.
[0004] Secondly, the adhesion of the aluminized layer has always been a problem that has plagued the packaging industry. The bonding between the aluminized layer and the substrate is not strong enough, and it is easy to fall off during use, which greatly reduces the durability and aesthetics of the packaging. This not only affects the market competitiveness of the product, but also brings inconvenience to consumers.
[0005] In addition, there are certain difficulties in recycling aluminized films. Due to the poor separation between the aluminized layer and the substrate, it is difficult to effectively separate and process the aluminized film during the recycling process, which increases the difficulty and cost of recycling. This is not only not conducive to the recycling of resources, but also aggravates the problem of environmental pollution.
[0006] In order to overcome the shortcomings of existing aluminized films, a new composite film with light-shielding and UV-protection functions is urgently needed in the market. This composite film needs to have good light-shielding and UV-protection properties to meet the needs of the high-end packaging market. At the same time, it should also have excellent processing properties and environmental protection properties to reduce production costs, reduce environmental pollution, and improve the durability and aesthetics of the packaging.
[0007] However, most of the composite films on the market are lacking in light-shielding and UV protection performance, and cannot meet the growing market demand. Although some composite films have certain light-shielding and UV protection functions, their performance is often not stable enough and is easily affected by environmental factors and changes. In addition, some composite films also have certain difficulties in the processing process, such as uneven coating, poor spraying effect, etc., which affect the quality and production efficiency of the product. Therefore, the development of a composite film and its preparation method that can meet the requirements of light-shielding and UV protection and overcome the shortcomings of existing aluminum-plated films has important practical significance and market value. Summary of the invention
[0008] In view of this, the present invention proposes a composite film with high light-shielding barrier properties that can replace aluminum plating and a preparation method thereof to solve the above-mentioned problems.
[0009] The technical solution of the present invention is achieved as follows: a light-shielding high-barrier composite film that can replace aluminum plating: comprising a base layer, a light-shielding layer, an ultraviolet protection layer and a protective layer arranged in sequence from the outside to the inside, the base layer is a polyvinyl chloride film layer with a thickness of 10-50 μm, the light-shielding layer is a mixture of montmorillonite nanoclay, a high molecular polymer and a nano-grade titanium dioxide dispersion liquid with a thickness of 5-20 μm, the ultraviolet protection layer is an ultraviolet absorber with a thickness of 3-15 μm, and the protective layer is a polyethylene terephthalate layer with a thickness of 8-30 μm.
[0010] Furthermore, the shading layer is made by mixing montmorillonite nanoclay, a high molecular polymer and a nano-scale titanium dioxide dispersion in a mass ratio of (3.5-5.5):(10-30):(0.1-0.8), the high molecular polymer is one of polyethylene, polypropylene or polystyrene, and the particle size of the nano-scale titanium dioxide dispersion is 5-50nm.
[0011] Furthermore, the ultraviolet absorber is prepared by mixing a bio-based material and a benzophenone compound or a triazole compound in a mass ratio of (1.2-2.0):(30-40).
[0012] Furthermore, the bio-based material is sugarcane extract, anthocyanin and chitosan in a mass ratio of (1.0-3.5):(0.2-0.8):(2.5-8.5).
[0013] Furthermore, the sugarcane extract is prepared by crushing sugarcane or bagasse, sieving to obtain coarse powder, using an ethanol solution with a mass concentration of 60-80% for immersion ultrasonic extraction, with a solid-liquid ratio of g / mL of 1:10-15, an extraction temperature of 50-80°C, an ultrasonic time of 25-35min, filtering and concentrating to obtain the sugarcane extract.
[0014] Furthermore, a method for preparing a light-shielding and high-barrier composite film that can replace aluminum plating comprises the following steps:
[0015] S1. preparing a base layer: preparing polyvinyl chloride into a polyvinyl chloride film as a base layer through an extrusion casting process;
[0016] S2, preparing a light-shielding layer: mixing montmorillonite nanoclay, high molecular polymer and nano-scale titanium dioxide dispersion evenly, and coating the mixture on a base layer through a coating process;
[0017] S3, preparing an anti-ultraviolet layer: covering the light-shielding layer with an ultraviolet absorber by a spraying process;
[0018] S4, preparing a protective layer: preparing polyethylene terephthalate into a film through an extrusion casting process, covering the anti-ultraviolet layer, and obtaining a composite film through hot pressing.
[0019] Furthermore, the temperature of the coating process of S2 is 50-80°C.
[0020] Furthermore, the spraying pressure of S3 is 0.20-0.40Mpa, and the spraying speed is 0.5-1.5m 2 / min.
[0021] Furthermore, the temperature of the hot pressing compounding of S4 is 120-180° C. and the pressure is 5-15 MPa.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) Excellent light-shielding and UV protection performance: The montmorillonite nanoclay in the light-shielding layer has a strong light-absorbing ability and can effectively block the transmission of visible light. The nano-scale titanium dioxide dispersion further enhances the light-shielding effect and also has a good scattering effect on ultraviolet rays. After combining with the high molecular polymer, a stable light-shielding structure is formed, ensuring that the composite film has excellent light-shielding performance and provides reliable protection for light-sensitive items; the bio-based materials in the UV protection layer work synergistically with benzophenone compounds or triazole compounds to efficiently absorb ultraviolet rays. Bio-based materials such as sugarcane extract, anthocyanin and chitosan are natural and environmentally friendly, and have good ultraviolet absorption capabilities. The nano-scale structure makes the composite film more comprehensive and effective in UV protection and significantly reduces the UV transmittance.
[0024] (2) Excellent processing performance: The preparation method of the composite film is simple and efficient, and the layers are tightly bonded and not easy to fall off. The combination of extrusion casting process and coating and spraying process makes the preparation process of the composite film more flexible, and the thickness and performance of each layer can be adjusted as needed to meet different application requirements.
[0025] This composite film has excellent light-shielding, UV-proof and processing properties, and is suitable for various packaging, sunshade, protection and other fields. Especially in the high-end packaging market, this composite film can replace the traditional aluminized film and provide products with more beautiful, durable and environmentally friendly packaging solutions. DETAILED DESCRIPTION
[0026] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0027] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0028] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0029] Example 1
[0030] A composite film with high light-shielding barrier that can replace aluminum plating, comprising a base layer, a light-shielding layer, an ultraviolet protection layer and a protective layer arranged in sequence from the outside to the inside, wherein the base layer is a polyvinyl chloride film layer with a thickness of 10 μm, the light-shielding layer is a mixture of montmorillonite nanoclay, a high molecular polymer and a nano-scale titanium dioxide dispersion liquid in a mass ratio of 3.5:10:0.1, the high molecular polymer is polyethylene, the particle size of the nano-scale titanium dioxide dispersion liquid is 5 nm, and the thickness is 5 μm, the ultraviolet protection layer is an ultraviolet absorber, and the ultraviolet absorber is a bio-based The bio-based material is mixed with a benzophenone compound or a triazole compound, and has a thickness of 3 μm. The bio-based material is a sugarcane extract, anthocyanin and chitosan in a mass ratio of 1.0:0.2:2.5; the sugarcane extract is obtained by taking sugarcane or bagasse, crushing it, and then sieving it to obtain a coarse powder, using a 60% ethanol solution for immersion ultrasonic extraction, the solid-liquid ratio g / mL is 1:10, the extraction temperature is 50°C, the ultrasonic time is 25 minutes, and filtering and concentrating to obtain the sugarcane extract; the protective layer is an ethylene glycol terephthalate layer with a thickness of 8 μm.
[0031] Example 2
[0032] A composite film with high light-shielding barrier that can replace aluminum plating, comprising a base layer, a light-shielding layer, an ultraviolet protection layer and a protective layer arranged in sequence from the outside to the inside, wherein the base layer is a polyvinyl chloride film layer with a thickness of 50 μm, the light-shielding layer is a mixture of montmorillonite nanoclay, a high molecular polymer and a nano-scale titanium dioxide dispersion liquid in a mass ratio of 5.5:30:0.8, the high molecular polymer is polypropylene, the particle size of the nano-scale titanium dioxide dispersion liquid is 50 nm, and the thickness is 20 μm, the ultraviolet protection layer is an ultraviolet absorber, and the ultraviolet absorber is a bio-based The bio-based material is mixed with a benzophenone compound or a triazole compound, and has a thickness of 15 μm. The bio-based material is a sugarcane extract, anthocyanin and chitosan in a mass ratio of 3.5:0.8:8.5; the sugarcane extract is obtained by taking sugarcane or bagasse, crushing it, and then sieving it to obtain a coarse powder, using an ethanol solution with a mass concentration of 80% for immersion ultrasonic extraction, the solid-liquid ratio g / mL is 1:15, the extraction temperature is 80°C, the ultrasonic time is 35 minutes, and filtering and concentrating to obtain the sugarcane extract; the protective layer is an ethylene glycol terephthalate layer with a thickness of 30 μm.
[0033] Example 3
[0034] A composite film with high light-shielding barrier that can replace aluminum plating, comprising a base layer, a light-shielding layer, an ultraviolet protection layer and a protective layer arranged in sequence from the outside to the inside, wherein the base layer is a polyvinyl chloride film layer with a thickness of 30 μm, the light-shielding layer is a mixture of montmorillonite nanoclay, a high molecular polymer and a nano-scale titanium dioxide dispersion liquid in a mass ratio of 4.5:20:0.5, the high molecular polymer is polystyrene, the particle size of the nano-scale titanium dioxide dispersion liquid is 25 nm, and the thickness is 15 μm, the ultraviolet protection layer is an ultraviolet absorber, and the ultraviolet absorber is a bio-based The material is mixed with a benzophenone compound or a triazole compound, and the thickness is 10 μm. The bio-based material is a sugarcane extract, anthocyanin and chitosan in a mass ratio of 2.5:0.5:5.5; the sugarcane extract is obtained by taking sugarcane or bagasse, crushing it, and then sieving it to obtain a coarse powder, using an ethanol solution with a mass concentration of 70% for immersion ultrasonic extraction, the solid-liquid ratio g / mL is 1:12, the extraction temperature is 70°C, the ultrasonic time is 30 minutes, and filtering and concentrating to obtain the sugarcane extract; the protective layer is an ethylene glycol terephthalate layer with a thickness of 20 μm;
[0035] The above examples 1-3 adopt the following preparation method:
[0036] S1. preparing a base layer: preparing polyvinyl chloride into a polyvinyl chloride film as a base layer through an extrusion casting process;
[0037] S2, preparing a light-shielding layer: after uniformly mixing montmorillonite nanoclay, high molecular polymer and nano-scale titanium dioxide dispersion, coating the mixture on the base layer by a coating process, the coating process temperature is 70° C.;
[0038] S3. Prepare the anti-ultraviolet layer: Cover the shading layer with the ultraviolet absorber by spraying, spraying 0.3Mpa, and the spraying speed is 1m 2 / min;
[0039] S4. Prepare a protective layer: After polyethylene terephthalate is made into a film through an extrusion casting process, it is covered on the UV protection layer, and a composite film is obtained by hot pressing and laminating. The temperature of the hot pressing and laminating is 150° C. and the pressure is 10 MPa.
[0040] Example 4
[0041] A composite film with high light-shielding barrier that can replace aluminum plating, comprising a base layer, a light-shielding layer, an ultraviolet protection layer and a protective layer arranged in sequence from the outside to the inside, wherein the base layer is a polyvinyl chloride film layer with a thickness of 30 μm, the light-shielding layer is a mixture of montmorillonite nanoclay, a high molecular polymer and a nano-scale titanium dioxide dispersion liquid in a mass ratio of 4.5:20:0.5, the high molecular polymer is polystyrene, the particle size of the nano-scale titanium dioxide dispersion liquid is 25 nm, and the thickness is 15 μm, the ultraviolet protection layer is an ultraviolet absorber, and the ultraviolet absorber is a bio-based The material is mixed with a benzophenone compound or a triazole compound, and the thickness is 10 μm. The bio-based material is a sugarcane extract, anthocyanin and chitosan in a mass ratio of 2.5:0.5:5.5; the sugarcane extract is obtained by taking sugarcane or bagasse, crushing it, and then sieving it to obtain a coarse powder, using an ethanol solution with a mass concentration of 70% for immersion ultrasonic extraction, the solid-liquid ratio g / mL is 1:12, the extraction temperature is 70°C, the ultrasonic time is 30 minutes, and filtering and concentrating to obtain the sugarcane extract; the protective layer is an ethylene glycol terephthalate layer with a thickness of 20 μm;
[0042] The above-mentioned Example 4 adopts the following preparation method:
[0043] S1. preparing a base layer: preparing polyvinyl chloride into a polyvinyl chloride film as a base layer through an extrusion casting process;
[0044] S2, preparing a light-shielding layer: after uniformly mixing montmorillonite nanoclay, high molecular polymer and nano-scale titanium dioxide dispersion, coating the mixture on the base layer by a coating process, the coating process temperature is 50° C.;
[0045] S3. Prepare the anti-ultraviolet layer: Cover the shading layer with the ultraviolet absorber by spraying, spraying at 0.20Mpa and a spraying speed of 0.5m 2 / min;
[0046] S4. Prepare a protective layer: After polyethylene terephthalate is made into a film through an extrusion casting process, it is covered on the UV protection layer, and a composite film is obtained by hot pressing and laminating. The temperature of the hot pressing and laminating is 120° C. and the pressure is 5 MPa.
[0047] Example 5
[0048] A composite film with high light-shielding barrier that can replace aluminum plating, comprising a base layer, a light-shielding layer, an ultraviolet protection layer and a protective layer arranged in sequence from the outside to the inside, wherein the base layer is a polyvinyl chloride film layer with a thickness of 30 μm, the light-shielding layer is a mixture of montmorillonite nanoclay, a high molecular polymer and a nano-scale titanium dioxide dispersion liquid in a mass ratio of 4.5:20:0.5, the high molecular polymer is polystyrene, the particle size of the nano-scale titanium dioxide dispersion liquid is 25 nm, and the thickness is 15 μm, the ultraviolet protection layer is an ultraviolet absorber, and the ultraviolet absorber is a bio-based The material is mixed with a benzophenone compound or a triazole compound, and the thickness is 10 μm. The bio-based material is a sugarcane extract, anthocyanin and chitosan in a mass ratio of 2.5:0.5:5.5; the sugarcane extract is obtained by taking sugarcane or bagasse, crushing it, and then sieving it to obtain a coarse powder, using an ethanol solution with a mass concentration of 70% for immersion ultrasonic extraction, the solid-liquid ratio g / mL is 1:12, the extraction temperature is 70°C, the ultrasonic time is 30 minutes, and filtering and concentrating to obtain the sugarcane extract; the protective layer is an ethylene glycol terephthalate layer with a thickness of 20 μm;
[0049] The above-mentioned Example 5 adopts the following preparation method:
[0050] S1. preparing a base layer: preparing polyvinyl chloride into a polyvinyl chloride film as a base layer through an extrusion casting process;
[0051] S2, preparing a light-shielding layer: after uniformly mixing montmorillonite nanoclay, high molecular polymer and nano-scale titanium dioxide dispersion, coating the mixture on the base layer by a coating process, the coating process temperature is 80° C.;
[0052] S3. Prepare the anti-ultraviolet layer: Cover the shading layer with the ultraviolet absorber by spraying, spraying 0.40Mpa, and the spraying speed is 1.5m 2 / min;
[0053] S4. Prepare a protective layer: After polyethylene terephthalate is made into a film through an extrusion casting process, it is covered on the UV protection layer, and a composite film is obtained by hot pressing and laminating. The temperature of the hot pressing and laminating is 180° C. and the pressure is 15 MPa.
[0054] Comparative Example 1
[0055] The difference between this comparative example and Example 3 is that the composite film does not contain a light-shielding layer.
[0056] Comparative Example 2
[0057] The difference between this comparative example and Example 3 is that the composite film does not contain an anti-ultraviolet layer.
[0058] Comparative Example 3
[0059] The difference between this comparative example and Example 3 is that the ultraviolet absorber does not contain bio-based materials.
[0060] Test Example 1-Optical Performance Test
[0061] 1. Light-shielding test method:
[0062] 1. Fix the composite film to be tested with a test fixture to ensure that it is flat and wrinkle-free;
[0063] 2. Place the fixed composite film between the light source and the illuminometer, keeping the same position and angle as the standard film test;
[0064] 3. Record the illuminance value displayed by the illuminometer at this time;
[0065] 4. Calculate the shading rate of the composite film to be tested, the formula is: shading rate = (1-illuminance value after passing through the film to be tested / background illumination value) × 100%; compare the shading rate of the composite film to be tested with the shading rate of the standard film to evaluate its shading performance.
[0066] 2. Anti-ultraviolet performance test:
[0067] 1. Prepare the sample: Cut the composite film into a size of 10cm*10cm, and ensure that its surface is flat, without wrinkles and damage to ensure the accuracy of the test.
[0068] 2. Test operation: Place the composite film on the test sample table of the spectrophotometer, set the test wavelength range to the ultraviolet region (200-400nm), and then conduct the test.
[0069] 3. Data Results
[0070] Table 1:
[0071]
[0072]
[0073] As can be seen from Table 1, the composite film of the embodiment group performs well in terms of light shielding rate and ultraviolet transmittance. The light shielding rates of Examples 1 to 5 are all 96.8% and above, and the light shielding rate of Example 3 is as high as 98.5%. In contrast, the light shielding rate of the comparative example group is significantly lower, with the light shielding rate of Comparative Example 1 being only 71.6%, and Comparative Example 2 and Comparative Example 3 being only 79.8% and 82.5%, respectively. This shows that the composite film of the embodiment group has significant advantages in blocking visible light and can provide better light shielding protection for the items in the package.
[0074] In terms of anti-ultraviolet performance, the ultraviolet transmittance of the embodiment group is below 4.5%, and the ultraviolet transmittance of embodiment 3 is as low as 3.5%. The ultraviolet transmittance of the comparative example group is relatively high, with the ultraviolet transmittance of comparative example 1 being 22.7%, and that of comparative example 2 being as high as 28.9%, and that of comparative example 3 being 15.2%. This shows that the composite film of the embodiment group can effectively block the penetration of ultraviolet rays, reduce the damage of ultraviolet rays to the items in the package, and is far superior to the comparative example group in terms of anti-ultraviolet performance.
[0075] Test Example 2-Barrier Performance Test
[0076] 1. Oxygen Transmission Rate Test
[0077] 1. Instruments and equipment: differential pressure gas permeameter;
[0078] 2. Sample preparation: Cut the composite film into a size of 5cm*10cm, and ensure that the surface of the sample is flat, without wrinkles or damage.
[0079] 3. Clamp the sample: Clamp the processed sample between the test chambers to ensure that the sample and the test chamber are well sealed and leak-free.
[0080] 4. Set test parameters: According to the test requirements, set the test temperature to 23°C, the pressure difference to 0.1MPa, and the test time to 2h.
[0081] 2. Water Vapor Transmission Rate Test
[0082] 1. Sample preparation: Cut the composite film into a size of 5cm*10cm to ensure that it can be tightly sealed on the moisture permeable cup. At the same time, clean and dry the moisture permeable cup and put an appropriate amount of desiccant in the moisture permeable cup.
[0083] 2. Seal the moisture permeable cup: Seal the mouth of the moisture permeable cup with the composite film to be tested to ensure a good seal without leakage.
[0084] 3. Initial weighing: Place the sealed moisture permeable cup on an analytical balance and weigh it, and record the initial mass.
[0085] 4. Place in a constant temperature and humidity chamber: Place the moisture permeable cup in a constant temperature and humidity chamber, set the temperature to 38°C and the relative humidity to 90%.
[0086] 5. Weighing: After 24 hours, take out the moisture permeable cup from the constant temperature and humidity chamber, weigh it on an analytical balance, and record the mass.
[0087] 3. Data Results
[0088] Table 2:
[0089] sample <![CDATA[Oxygen transmission rate (cm 3 / m 2 ·d·Pa)]]> <![CDATA[Water vapor transmission rate (g / m 2 ·d)]]> Example 1 2.1 1.9 Example 2 1.8 1.5 Example 3 1.2 0.9 Example 4 1.5 1.1 Example 5 2.2 1.8 Comparative Example 1 3.9 3.1 Comparative Example 2 4.1 3.0 Comparative Example 3 3.2 2.8
[0090] The composite films of the embodiment group have significantly lower oxygen permeability and water vapor permeability than the comparative group. The oxygen permeability of the composite films of the embodiment 1 to the embodiment 5 is between 1.2 and 2.2 cm 3 / (m 2 ·d·Pa), water vapor transmission rate is 0.9-1.9g / m 2 ·d. The oxygen permeability of the comparative group is between 3.2-4.1cm 3 / (m 2 ·d·Pa), water vapor transmission rate is 2.8-3.1g / m 2 This indicates that the composite film of the embodiment group has better barrier properties against oxygen and water vapor.
[0091] In summary, the montmorillonite nanoclay in the light-shielding layer reduces the amount of light transmitted by reflecting and scattering light, thereby realizing the light-shielding function; nano-scale titanium dioxide has excellent ultraviolet shielding performance, it can absorb and scatter ultraviolet rays, and reduce the transmission of ultraviolet rays; when ultraviolet rays are irradiated on the composite film, nano-scale titanium dioxide can convert the energy of ultraviolet rays into heat energy or other forms of energy, thereby reducing the transmittance of ultraviolet rays. Montmorillonite nanoclay and nano-scale titanium dioxide work together in the light-shielding layer, and synergistically enhance the anti-ultraviolet performance. Montmorillonite nanoclay mainly absorbs visible light, while nano-scale titanium dioxide focuses on shielding ultraviolet rays. The combination of the two can achieve effective light-shielding and anti-ultraviolet effects in a wider spectrum range. The polymer plays a bonding and supporting role in the light-shielding layer. It combines montmorillonite nanoclay and nano-scale titanium dioxide dispersion to form a stable structure. At the same time, the polymer can also improve the mechanical strength and toughness of the light-shielding layer, making the composite film more durable and not easy to break during use. The ultraviolet absorber in the anti-ultraviolet layer can absorb ultraviolet rays within a specific wavelength range, convert the energy of ultraviolet rays into harmless heat or other forms of energy, thereby reducing the amount of ultraviolet rays passing through the composite film, and the bio-based material can enhance the stability of the anti-ultraviolet layer and the ability to absorb ultraviolet rays through the sugarcane extract, anthocyanin and chitosan. The composite film of the present invention can be widely used in the field of product packaging with high requirements for light-shielding, ultraviolet protection and barrier properties.
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite film with high light-shielding and barrier properties that can replace aluminum plating, characterized by: The invention comprises a base layer, a light-shielding layer, an anti-ultraviolet layer and a protective layer which are arranged in sequence from the outside to the inside. The base layer is a polyvinyl chloride film layer with a thickness of 10-50 μm. The light-shielding layer is a mixture of montmorillonite nanoclay, a high molecular polymer and a nano-grade titanium dioxide dispersion with a thickness of 5-20 μm. The anti-ultraviolet layer is an ultraviolet absorber with a thickness of 3-15 μm. The protective layer is a polyethylene terephthalate layer with a thickness of 8-30 μm.
2. A light-shielding, high-barrier composite film that can replace aluminum plating as claimed in claim 1, characterized in that: The shading layer is made of a mixture of montmorillonite nanoclay, a high molecular polymer and a nano-scale titanium dioxide dispersion in a mass ratio of (3.5-5.5):(10-30):(0.1-0.8), the high molecular polymer is one of polyethylene, polypropylene or polystyrene, and the particle size of the nano-scale titanium dioxide dispersion is 5-50nm.
3. A light-shielding, high-barrier composite film that can replace aluminum plating as claimed in claim 1, characterized in that: The ultraviolet absorber is prepared by mixing a bio-based material and a benzophenone compound or a triazole compound in a mass ratio of (1.2-2.0):(30-40).
4. A light-shielding, high-barrier composite film that can replace aluminum plating as claimed in claim 3, characterized in that: The bio-based materials are sugarcane extract, anthocyanin and chitosan in a mass ratio of (1.0-3.5):(0.2-0.8):(2.5-8.5).
5. A light-shielding, high-barrier composite film that can replace aluminum plating as claimed in claim 4, characterized in that: The sugarcane extract is prepared by crushing sugarcane or bagasse, sieving to obtain coarse powder, using an ethanol solution with a mass concentration of 60-80% for immersion ultrasonic extraction, with a solid-liquid ratio of g / mL of 1:10-15, an extraction temperature of 50-80°C, an ultrasonic time of 25-35 minutes, filtering and concentrating to obtain the sugarcane extract.
6. The method for preparing a light-shielding, high-barrier composite film that can replace aluminum plating as claimed in claim 1, characterized in that: The following steps are involved: S1. preparing a base layer: preparing polyvinyl chloride into a polyvinyl chloride film as a base layer through an extrusion casting process; S2, preparing a light-shielding layer: mixing montmorillonite nanoclay, high molecular polymer and nano-scale titanium dioxide dispersion evenly, and coating the mixture on a base layer through a coating process; S3, preparing an anti-ultraviolet layer: covering the light-shielding layer with an ultraviolet absorber by a spraying process; S4, preparing a protective layer: preparing polyethylene terephthalate into a film through an extrusion casting process, covering the anti-ultraviolet layer, and obtaining a composite film through hot pressing.
7. The method for preparing a light-shielding, high-barrier composite film that can replace aluminum plating as claimed in claim 6, characterized in that: The temperature of the coating process of S2 is 50-80°C.
8. The method for preparing a light-shielding, high-barrier composite film that can replace aluminum plating as claimed in claim 6, characterized in that: The spraying speed of S3 is 0.20-0.40Mpa and 0.5-1.5m 2 / min.
9. The method for preparing a light-shielding, high-barrier composite film that can replace aluminum plating as claimed in claim 6, characterized in that: The temperature of the hot pressing compound of S4 is 120-180° C. and the pressure is 5-15 MPa.
Citation Information
Patent Citations
Biologically-ultraviolet-proof blusher cosmetic composition and preparation method thereof
CN105232396A
Halogen-free flame-retardant high shading PC composite material and preparation method thereof
CN109337330A
Light-blocking low-oxygen permeable material and composite sheet for packaging cheese at normal temperature
CN113334890A
Red and ultraviolet blocking agent and preparation method of PET (Polyethylene Terephthalate) blocking membrane
CN117089268A